A role for SPEECHLESS in the integration of leaf stomatal patterning with the growth vs disease trade-off in poplar - McKown, Athena D; Klápště, Jaroslav; Guy, Robert D; Corea, Oliver R A; Fritsche, Steffi; Ehlting, Jürgen; El-Kassaby, Yousry A; Mansfield, Shawn D (New phytologist, 2019)
Occurrence of stomata on both leaf surfaces (amphistomaty) promotes higher stomatal conductance and photosynthesis while simultaneously increasing exposure to potential disease agents in black cottonwood (Populus trichocarpa). A genome-wide association study (GWAS) with 2.2M single nucleotide polymorphisms generated through whole-genome sequencing found 280 loci associated with variation in adaxial stomatal traits, implicating genes regulating stomatal development and behavior. Strikingly, numerous loci regulating plant growth and response to biotic and abiotic stresses were also identified. The most significant locus was a poplar homologue of SPEECHLESS (PtSPCH1). Individuals possessing PtSPCH1 alleles associated with greater adaxial stomatal density originated primarily from environments with shorter growing seasons (e.g. northern latitudes, high elevations) or with less precipitation. PtSPCH1 was expressed in developing leaves but not developing stem xylem. In developing leaves, RNA sequencing showed patterns of coordinated expression between PtSPCH1 and other GWAS-identified genes. The breadth of our GWAS results suggests that the evolution of amphistomaty is part of a larger, complex response in plants. Suites of genes underpin this response, retrieved through genetic association to adaxial stomata, and show coordinated expression during development. We propose that the occurrence of amphistomaty in P. trichocarpa involves PtSPCH1 and reflects selection for supporting rapid growth over investment in immunity.
Keywords: Quantitative Trait, Heritable; Plant Development; druhová specificita; Genome-Wide Association Study; kvantitativní znak dědičný; Alleles; genotyp; Genotype; Phenotype; Species Specificity; zeměpis; Climate; Geography; vývoj rostlin; Genes, Plant; Populus; Polymorphism, Single Nucleotide; celogenomová asociační studie; imunita rostlin; alely; jednonukleotidový polymorfismus; průduchy rostlin; rostlinné geny; Plant Immunity; Plant Proteins; Gene Expression Regulation, Plant; rozvržení tělního plánu; podnebí; regulace genové exprese u rostlin; fenotyp; Body Patterning; Plant Stomata; rostlinné proteiny